2013
DOI: 10.1080/00909882.2013.854400
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effects of the Addition of Videos to a Website Promoting Environmental Breast Cancer Risk Reduction Practices: Are Videos Worth It?

Abstract: Searching for ways to reach wider audiences in more comprehensible ways, health promotion agencies might add videos to their current web offerings. While potentially costly and time consuming to create, the effect of these videos on websites has not received much attention. This study translated research about the potential breast cancer risk for young girls associated with the household chemical PFOA into two websites mothers with young daughters were randomly assigned to view (website with videos vs. website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Educational videos and animation employed in the context of health care have been shown to increase patients’ knowledge of their own condition and their compliance with care [58,59], recall of oncology information [60], decision making, and self-efficacy [61]. However, audio visual material was only incorporated into 11% (9/85) of the sites evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Educational videos and animation employed in the context of health care have been shown to increase patients’ knowledge of their own condition and their compliance with care [58,59], recall of oncology information [60], decision making, and self-efficacy [61]. However, audio visual material was only incorporated into 11% (9/85) of the sites evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have either assessed specific websites, such as particular online media outlets 47 or specific chemicals. 48 To our knowledge, our study is the first to focus on multiple, suspected environmental risk factors to assess the current state of information available on the Internet. Our comprehensive analysis found that webpages were generally credible and contained information on research studies mainly from studies popularized by the media.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to environmental factors related to breast cancer risk, research has focused either on certain environmental factors, effects of visual presentation in communication of health risk, or information available in the news media. 47,48 Accuracy of content, readability, and cultural sensitivity are important for the communication of environmental risks of breast cancer because of the variety of environmental exposures studied, the debate on the conclusiveness of current findings, misinterpretation of findings in the media. 49 Effective environmental risk communication for breast cancer also underscores the need for more research and collaboration between clinicians, health educators, and media professionals for improved public knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…They need help learning to facilitate these conversations in a health-promoting manner. Third-party, online, community-based approaches may be ideal in both disseminating environmental risk information and helping mothers and daughters navigate breast cancer risk conversations to promote their adoption of risk-reducing behaviors [ 6 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers have reported that using third-party approaches like magazine articles helps them start conversations with their daughters and also enhances daughters’ comfort level with the topic of risk [ 2 , 6 ]. Studies also indicate that third-party, web-based approaches about environmental factors and breast cancer risk (e.g., videos about radiation risk and BPA/perfluorooctanoic acid) can positively affect mothers’ and daughters’ risk-reducing behavior [ 9 , 10 ]. Third-party approaches accessed online may be ideal as mothers report that the Internet is a primary source of health information, including when seeking breast cancer risk knowledge [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%